IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DI MADRASAH IBTIDAIYAH / IMPLEMENTATION OF THE INDEPENDENT LEARNING CURRICULUM IN PRIMARY SCHOOLS - Qur'ani, Muhammad Nuzulul; Basri, Hasan; Mohammad Ilham Al Ghifary; Togar Siagian (Al-Mudarris: Journal Of Education, 2024)
The independent learning curriculum has become the main focus in efforts to reform education in Indonesia. This article aims to find out and analyze how the Independent Learning Curriculum is implemented in Islamic Cultural History (SKI) lessons at the MIN 2 Bantul School. This study uses a qualitative approach by collecting data through interviews, observation, and document analysis. The results of this study reveal that the implementation of the independent learning curriculum in SKI lessons at MIN 2 Bantul has brought about significant changes in the learning approach. Teachers are freer to design lessons that suit student needs and local conditions. Project-based learning methods, collaborative learning, and problem-based learning have become more common and result in students' active involvement in learning. In addition, learning evaluation in the context of the Independent Learning curriculum has changed to focus more on measuring student competence. Regular formative assessments provide meaningful feedback. Meanwhile, competency-based summative assessments measure understanding of concepts and application of knowledge in practical contexts. The challenges faced in implementation include the need for more in-depth teacher training in innovative learning strategies and the use of technology. In addition, continuous monitoring and ongoing support from the school and government are needed to ensure the full success of implementing the independent learning curriculum in SKI lessons at MIN 2 Bantul.